Mechanisms underlying melatonin-mediated prevention of fenvalerate-induced behavioral and oxidative toxicity in zebrafish. Issue 23 (17th December 2017) - Han, Jingjing; Ji, Cheng; Guo, Yichen; Yan, Rui; Hong, Ting; Dou, Yuanyan; An, Yan; Tao, Shasha; Qin, Fenju; Nie, Jihua; Ji, Chen; Wang, Han; et al.
ABSTRACT: The neurotoxic effects attributed to the pesticide fenvalerate (FEN) are well-established. The aim of this study was to determine whether melatonin (MLT) was able to protect against FEN-induced behavior, oxidative stress, apoptosis, and neurogenesis using zebrafish ( Danio rerio ) model. Zebrafish exposed to 100 μg/L FEN for 120 h exhibited decreased swimming activity accompanied by downregulated expression of neurogenesis-related genes (Dlx2, Shha, Ngn1, Elavl3, and Gfap), suggesting that neurogenesis were impaired. In addition, FEN exposure significantly elevated oxidative stress as evidenced by increased malondialdehyde levels, as well as activities of Cu/Zn superoxide dismutase (Cu/Zn SOD), catalase, and glutathione peroxidase. Acridine orange staining demonstrated that embryos treated with FEN for 120 h significantly enhanced apoptosis mainly in the brain. FEN also produced upregulation of the expression of the pro-apoptotic genes (Bax, Fas, caspase 8, caspase 9, and caspase 3) and decreased expression of the anti-apoptotic gene Bcl-2. MLT significantly attenuated the FEN-mediated oxidative stress, modulated apoptotic-regulating genes, and diminished apoptotic responses. Further, MLT blocked the FEN-induced effects on swimming behavior as well as on neurogenesis-related genes. In conclusion, MLT protected against FEN-induced developmental neurotoxicity and apoptosis by inhibiting pesticide-mediated oxidative stress in zebrafish.